2020
DOI: 10.1016/j.breast.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer surveillance for BRCA1/2 mutation carriers – is “early detection” early enough?

Abstract: Background Annual MRI screening is associated with a significant reduction in advanced-stage breast cancer diagnosis in BRCA1/2 mutation carriers. The impact that early detection has on subsequent oncological treatment is less frequently reported. In this study we compared disease stage and therapeutic approaches in BRCA1/2 mutation carriers who developed breast cancer while adhering to the recommended surveillance scheme (“known carriers”), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It is debated whether the detection of a breast cancer in a woman choosing surveillance is early enough. Even under tight surveillance the breast cancer diagnosed in BRCA patients are more aggressive and therefore more often require adjuvant chemo- and/or endocrine therapy [ 98 ].…”
Section: Surveillance As An Alternative To Risk Reducing Surgery In Female With Brca Mutationmentioning
confidence: 99%
“…It is debated whether the detection of a breast cancer in a woman choosing surveillance is early enough. Even under tight surveillance the breast cancer diagnosed in BRCA patients are more aggressive and therefore more often require adjuvant chemo- and/or endocrine therapy [ 98 ].…”
Section: Surveillance As An Alternative To Risk Reducing Surgery In Female With Brca Mutationmentioning
confidence: 99%
“…Heemskerk-Gerritsen et al found that RRM was associated with lower overall (hazard ratio 0.4) and breast cancer-specific (hazard ratio 0.06) mortality for BRCA1 P/LPV carriers, but not BRCA2 P/LPV carriers in a multicenter cohort study [ 46 ]. As expected, lower cancer rates would result in lower rates of cancer treatment [ 47 , 48 ], which can be associated with significant morbidity and reduced quality of life. Skin-sparing mastectomy with or without nipple-areolar complex preservation followed by immediate breast reconstruction is becoming the preferred surgical approach given the superior cosmetic results [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 79%
“…The impact of MRI screening on survival is not clear, despite the stage shift at diagnosis. Although a small retrospective study from Israel suggested a possible survival advantage for BRCA P/LPV carriers who decline RRM and develop breast cancer during intensive follow-up compared with unscreened carriers (unaware of their genetic status) [ 47 ], a larger study from another tertiary center in Israel did not demonstrate the same positive outcomes [ 48 ]. Potential disadvantages for MRI use at annual intervals include higher costs compared with mammography (MG), higher false-positive rates [ 81 ], and limited availability in certain geographical regions within the country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost analysis upon which the decision-making model was built has much greater importance in the investigated setting where efficacy data are controversial, such as long-term survival in the various clinical paths. In the context of BRCA-mutated subjects, the pathway with the addition of periodic MRI leads to a higher number of early T1N0 diagnoses (56.3% vs. 29.2%), in diagnosis-positive lymph nodes (11.5% vs. 48.5%), and to a lower number of chemotherapies administered (47.9% vs. 80.2%) [ 55 ]. However, despite these data, the real impact of MRI on mortality reduction is still uncertain, particularly in BRCA2 carriers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%